2. Antibacterial Test of Red Dragon Fruit Extract Peel (Hylocereus polyrhizus) Against Bacteria Salmonella pullorum - Ichsan Maulana; Abdul Harris; Fakhrurrazi Fakhrurrazi; Maryulia Dewi; Safika Safika; Erina Erina; Muhammad Jalaluddin (Universitas Syiah Kuala, 2018)
The purpose of this study is to determine the effect of the red dragon fruit peels (Hylocereus polyrhizus) extract on the growth of Salmonella pullorum. This research was conducted at the Laboratory of Microbiology, Veterinary Faculty, University of Syiah Kuala, Banda Aceh. Red dragon fruit peels that used in this study is obtained from ripe fruit and Salmonella pullorum cultures is obtained from Microbiology Laboratory of Veterinary Faculty Unsyiah. Salmonella pullorum culture added evenly on the surface of Mueller Hinton Agar, the number of the bacteria have been standarized using Mc Farland'1 method. Discs soaked in the red dragon fruit peels extracts at different concentrations (20 mg/ml, 40 mg/mL, and 60 mg/ml). Ampicillin is used as positive controls and DMSO (dimethyl sulfoxide) was placed on the surface of Mueller Hinton Agar. The parameters in this study is the inhibition zone diameter. Data were analyzed descriptively. The results showed that the red dragon fruit peel extract is able to inhibit the growth of Salmonella pullorum and the average of inhibition diameter zone at a concentration 60 mg / ml is 9.6 mm, 40 mg / ml is 9.4 mm and 20 mg / ml is 9.3 mm